Organochlorines And Thiamine In Salmon (Salmo Salar L.) And Prey Species, Baltic Herring (Clupea Harengus L.) And Sprat (Sprattus Sprattus (L.)), In Connection With The M74 Syndrome ... - Vuorinen, Pekka J.; Paasivirta, Jaakko; Keinänen, Marja; Vartiainen, Terttu; Parmanne, Raimo (ASC 1999 - U - Theme session, 2024)
No abstracts are to be cited without prior reference to the author.Yolk-sac fry mortality in salmon from the River Simojoki emptying into the northeastern Gulf ofBothnia, northern Baltic Sea, has been monitored and female muscle organochlorine (OC) and egg thiamine concentrations analysed in samples from certain years. OC and thiamine contents in the salmon prey species, Baltic herring and sprat, from the years of high M74 incidence have also been analysed. The proportion of females producing yolk-sac fry with M74 mortality has fluctuated in the period 1991/92 - 1998/99 from 31 to 92% and the mean annual yolk-sac fry mortality from 19 to 76%. OCs, especially dioxin-like ones in female muscle, increased at the same time as the M74 mortality. Salmon egg thiamine concentration correlated negatively with the M74 mortality of the respective yolk-sac fry. Baltic herring and sprat caught from late autumn to early winter contained thiamine, 8.6, and 6.9 nmol g-1, respectively. Concentrations of total PCB and PCDD ...